FAILURE ANALYSIS OF FRACTURE FOR CLUTCH SLEEVE PLATE - WANG XiaoLi; MU Rui; WANG CaiHong (Jixie qiangdu)
Sleeve plate of clutch disk is studied in this paper,according to the fracture problems of sleeve plate by carbonitriding and phosphating treatment,the fractured sleeve plate was analyzed by means of fracture macroscopic analysis,fracture microscopic analysis,metallographic analysis,hardness testing and chemical composition analysis of material. The results show that the fracture of sleeve plate occurs before surface phosphating treatment,crack starts at left part of round window for sleeve plate,and it extends to run through the fracture in the process of production. In addition,due to cylindrical section is smaller and the surface area adopts hardening treatment,when the surface area is subjected to abnormal impact,it is very easy to cause the cracking of sleeve plate,especially the coarse structure leads to the increase of brittleness and it increases the probability of cracking of the parts.